Effect of Scraper Geometry on Scraping HAP/ZrO2 Slurry in Digital Light Processing. (20th December 2021) - Gu, Hai; Zhang, Jie; Sun, Jianhua; Huang, Tiancheng; Jiang, Jie; Li, Bin; Wu, Weiwei
Abstract : Digital light processing (DLP) can be used to form HAP/ZrO2 mixed ceramic slurry. In the printing technology, the scraper geometry has an important effect on the scraping process; thus, it is necessary to conduct analysis. A modified lattice Boltzmann method (LBM) is proposed to conduct the numerical simulations according to the non-Newtonian behavior of the slurry. The Cross behavior of the slurry is viewed as a special external force; then, the traditional LBM including the true external force can be utilized effectively. The triangle, rectangle, trapezium, and rounded rectangle are the main considered section geometries of the scraper. When the flow velocity is set to 0.1 m/s, the results show that the maximum velocity occurs near the bottom surface of the scraper. In four situations, the velocity peak of the triangle case is 0.6270 m/s, which is the maximum, and much larger than the flow velocity of 0.1 m/s. The velocity peak of the rectangle case is 0.0466 m/s, which is the minimum. Although the velocity peak of the rounded rectangle case is 0.0556 m/s, the second velocity peak is 0.0465 m/s; the difference is smaller than that of the rectangle case. In addition, the streamlines figures show that the sharp corner leads to the obvious velocity change. In summary, the rounded rectangle is considered to be more suitable for scraping the HAP/ZrO2 mixed slurry.